Modified QLRS-APM: A Proposal to Avoid Initiating Route Error Messages to Source in Mobile Ad Hoc Networks - Shahariar, Rezvi; Anwar, Shahed (Dhaka University Journal of Science, 2015)
Existing local route repair schemes such as localized route repair (LRR), ad hoc on-demand distance vector-backup routing (AODV-BR), and witness-aided routing (WAR) can be incorporated with reactive routing protocols to repair route breakages on ongoing routes. All of these schemes have some problems in local route repairing such as long delay, excessive energy consumption etc. To mitigate these problems in existing local route repair schemes, quick local repair scheme using adaptive promiscuous mode (QLRS-APM) is proposed. QLRS-APM is a novel approach in local route repairing but sometimes generates unnecessarily route error to the source. This paper provides a solution by giving an extension on QLRS-APM to avoid initiating route error messages to the source and also at the same time reducing excessive energy consumption from the network. DOI: http://dx.doi.org/10.3329/dujs.v62i1.21963 Dhaka Univ. J. Sci. 62(1): 59-64, 2014 (January)